Burning Rate Constants and Microexplosion Phenomena Measurements of Droplet Combustion - Fidari Rosyadi, Basthiyan Sidqi; Wardana, I Nyoman Gede Wardana; Shy, Shenqyang (Steven) (Jurusan Teknik Mesin, Fakultas Teknik, Universitas Brawijaya, 2014)
This study investigates experimentally droplet combustion in a quiescent atmosphere using diesel oil (DO), biodiesel oil (BO), and sunflower oil (SO). Symmetrically spherical droplets with diameters varying from 0.3 mm to 0.6 mm are generated by a home-built piezoelectrically-driven droplet generator. Before a run, the small droplet is suspended at the intersection of two very fine horizontally-positioned, perpendicularly-aligned ceramic fibers of 20 Âµm in diameter. A run begins at a time when a diffusional flame is just established to envelop the suspended droplet using an electrically-controlled and automaticallyremoved heating device. A high-speed camcorder is used to record the time evolution of droplet burning process. Results show that after flame envelope the droplet where initial diameter (d ) is determined, DO and BO droplet instantaneous diameters (d) just shrink with increasing time, where plot for d 0 law give linear slope indicate that DO and BO can be assumed as singlecomponent fuel with burning rate constants value, but SO which is multicomponent fuels, give two kinds slope from d -law plot indicate that there are two value burning rate constants, namely K 1 2 for first stage of burning rate constant and K 2 for second stage of burning rate constant.Keywords: Droplet combustion, Burning Rate Constant, Microexplosion.